Perancangan Ulang Fasilitas Kereta Galon Dengan Pendekatan Konsep Ergonomi di PT.XYZ - Sinambela, Sahat (Journal of Academia Perspectives, 2022)
Gallon Stroller (Troly) used in PT. XYZ to transport gallons of packaged drinks between work stations, initial data was obtained from research at the workplace of the operator experiencing complaints of MSDs Musculoskeletal Disorders, then after conducting research on the assessment of the Nurdic Body Mapping (NBM) score, the average was above 48% and 43%, the results analysis of work postures and with Rapid Upper Limb Assessment REBA all work systems have high complaints scores so they must be repaired immediately, using anthropometric size considerations it is also found that the size of the operator and the size of the tool experience significant differences, after an analysis of work postures is not ideal and needs to be improved immediately, to achieve the ideal working posture by redesigning the stroller, taking into account the previous anthropometric data of height, 296 cm, and length. 359 cm, changed to 370.6 cm and the addition of assistive devices as a footstool to overcome MSDs Musculoskeletal Disorders, and changing the method to work, a stroller is proposed from a manual drive using an electric motor and a new grip design, with anthropometric concepts, and REBA analysis. after the use of the new design was analyzed with the concept of percentile and REBA, all work postures decreased from very high complaints level reaching 13 on a risk scale to 4 low